PEMBANGUNAN BERKELANJUTAN MENJADI DASAR TERINTEGRASI DALAM PEMBANGUNAN SUATU WILAYAH BERDASARKAN UNDANG-UNDANG NO. 32 TAHUN 2009 TENTANG PERLINDUNGAN DAN PENGELOLAAN LINGKUNGAN HIDUP - Farahwati Farahwati (Universitas 17 Agustus 1945 Samarinda, 2020)
The environment on earth as regulated in Law No. 32 of 2009concerning Environmental Protection and Management, thatenvironmental management consists of the natural environment inaccordance with the understanding of ecosystem life and socialenvironment that is illustrated by the existence of human groups both insociety and in families and refers to the understanding of humanity(humanism), so that includes understanding about between nations,interregion and the built environment (originally thought to be man-made;man-made environment).Development needs to pay attention to environmental conditionsthat exist from the physical side (soil, water, air), biotics (flora, fauna),and culture (culture, interactions between people). Environmental qualityconditions will tend to continue to decline if not balanced with the conceptof sustainable development planning in an effort to preserve the existingenvironmental functions.The implementation of environmentally sound development and thecontrolled use of natural resources wisely is the main objective ofenvironmental management. Sustainable development is very closelyrelated to environmental management programs and policies.The nature of environmental law enforcement in sustainabledevelopment covers all environmental law systems with the aim ofprotecting and properly managing the environment and is an activity toimplement and apply just environmental laws and take legal actionagainst any violations or deviations of law committed by legal subjectseither through judicial procedures or through non-judicial procedures.Legal norms are the most dominant rules that are enforced with powerand for their violations subject to certain sanctions that have beenestablished by the State.